Synthesis of Ag‐loaded tungsten oxide microspheres and their improved photocatalytic activity. (15th January 2020) - She, Yu; Zhu, Yufu; Zhou, Lei; Yuan, Yuanmi; Hao, Jing; Jiang, Qingsong
Abstract : In this study, tungsten oxide microstructures/nanostructures with different morphologies were prepared by the hydrothermal synthesis methods. The morphologies and structures of the obtained products were characterised by field‐emission scanning electron microscopy and X‐ray diffraction. The photocatalytic properties of tungsten oxide microstructures/nanostructures were characterised by the degradation of rhodamine B solution. The results indicate that tungsten oxide microspheres prepared by using tungstic acid and hydrogen peroxide solution as raw materials show the highest photocatalytic activity. By changing the concentration of tungstic acid used in the synthesis process, the morphologies of tungsten oxide microspheres can be controlled. The influences of the amount of chemical reagent addition on its morphology and catalytic properties were discussed. In order to further improve the photocatalytic activity of the samples, Ag nanoparticles were loaded on the obtained tungsten oxide microspheres. The photocatalytic experiment results indicate that the photocatalytic performance of tungsten oxide was improved by Ag loading. The results indicate that Ag‐loaded tungsten oxide microspheres are favourable for their photocatalytic applications.